The topologization of the space of separately continuous functions - Voloshyn, H.A.; Maslyuchenko, V.K. (Carpathian Mathematical Publications, 2013)
Here we introduce locally convex topology T of the layer uniform convergence on the space S = CC [0,1] ^ 2 of all separately continuous functions f: [0,1] ^ 2 → R, we prove that the space (S, T) is complete and it is not metrizable one, the space P of all polynomials of two variables on [0,1] ^ 2 is everywhere dense in S , and so, S is separable.